Hodnocení stavebně technického stavu existujícího objektu - Janáč, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2023)
Teoretická část mé bakalářské práce se zabývá historií, vývojem a zkoušením zdiva, zejména pórobetonového a škvárobetonového, z něhož je velká část hodnoceného objektu postavena. V praktické části se práce zaměřuje na samotné hodnocení stávajícího stavu objektu, zejména pomocí vizuální defektoskopie, návrhem stavebních opatření a vhodností jeho případného budoucího užívání.

The theoretical part of my bachelor's thesis deals with the history, development and testing of masonry, especially aerated concrete and cinder block masonry, of which a large part of the evaluated building is constructed. In the practical part, the thesis focuses on the actual assessment of the existing condition of the building, especially by means of visual defectoscopy, the design of measures and the suitability of its possible future use.
Evaluation of the construction and technical condition of the existing building
Keywords: Stavební objekt; konstrukce; diagnostika; trhlina; vizuální defektoskopie; rodinný dům; stavební průzkum; pórobeton; Building object; construction; diagnostics; crack; visual defectoscopy; detached house; building survey; aerated concrete